Peroxisomal biogenesis is genetically and biochemically linked to carbohydrate metabolism in Drosophila and mouse. - Michael F Wangler; Yu-Hsin Chao; Vafa Bayat; Nikolaos Giagtzoglou; Abhijit Babaji Shinde; Nagireddy Putluri; Cristian Coarfa; Taraka Donti; Brett H Graham; Joseph E Faust; James A McNew; Ann Moser; et al. (PLoS Genetics, 2017)
Peroxisome biogenesis disorders (PBD) are a group of multi-system human diseases due to mutations in the PEX genes that are responsible for peroxisome assembly and function. These disorders lead to global defects in peroxisomal function and result in severe brain, liver, bone and kidney disease. In order to study their pathogenesis we undertook a systematic genetic and biochemical study of Drosophila pex16 and pex2 mutants. These mutants are short-lived with defects in locomotion and activity. Moreover these mutants exhibit severe morphologic and functional peroxisomal defects. Using metabolomics we uncovered defects in multiple biochemical pathways including defects outside the canonical specialized lipid pathways performed by peroxisomal enzymes. These included unanticipated changes in metabolites in glycolysis, glycogen metabolism, and the pentose phosphate pathway, carbohydrate metabolic pathways that do not utilize known peroxisomal enzymes. In addition, mutant flies are starvation sensitive and are very sensitive to glucose deprivation exhibiting dramatic shortening of lifespan and hyperactivity on low-sugar food. We use bioinformatic transcriptional profiling to examine gene co-regulation between peroxisomal genes and other metabolic pathways and we observe that the expression of peroxisomal and carbohydrate pathway genes in flies and mouse are tightly correlated. Indeed key steps in carbohydrate metabolism were found to be strongly co-regulated with peroxisomal genes in flies and mice. Moreover mice lacking peroxisomes exhibit defective carbohydrate metabolism at the same key steps in carbohydrate breakdown. Our data indicate an unexpected link between these two metabolic processes and suggest metabolism of carbohydrates could be a new therapeutic target for patients with PBD.